1991
DOI: 10.1002/ajmg.1320380125
|View full text |Cite
|
Sign up to set email alerts
|

Fucosidosis revisited: A review of 77 patients

Abstract: Fucosidosis is a rare, autosomal recessive, lysosomal storage disorder caused by a severe deficiency of alpha-L-fucosidase in all tissues. We have conducted a review of fucosidosis, compiling data from published reports and an international questionnaire survey. Seventy-seven patients affected with fucosidosis of which 19 had not been reported before have been identified. A major aim of the present study was to define the natural history of fucosidosis. The clinical picture of fucosidosis consists of progressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
128
0
4

Year Published

1999
1999
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 151 publications
(141 citation statements)
references
References 103 publications
9
128
0
4
Order By: Relevance
“…5,6 All but two mutations were found in homozygous form, confirming the very high rate of consanguinity found in fucosidosis families. 4 The different mutations are discussed below. The patients' initials refer to the appendix table in the review study by Willems et al 4 …”
Section: Fucosidosis Mutationsmentioning
confidence: 99%
See 3 more Smart Citations
“…5,6 All but two mutations were found in homozygous form, confirming the very high rate of consanguinity found in fucosidosis families. 4 The different mutations are discussed below. The patients' initials refer to the appendix table in the review study by Willems et al 4 …”
Section: Fucosidosis Mutationsmentioning
confidence: 99%
“…Additional features are angiokeratoma corporis diffusum, dysostosis multiplex, visceromegaly, ocular abnormalities, hearing loss, seizures, coarse features, recurrent infections, spasticity, contractures, growth retardation, muscle wasting and dystrophy. [2][3][4] All these clinical abnormalities are progressive, leading to cachexia and early death. Although clinical heterogeneity with a very rapidly progressive course and death in infancy (type I), and a slightly milder variant with death in adulthood (type II) has been described, further studies have shown that fucosidosis has a wide continuous clinical spectrum without any evidence for real clinical heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1,2 Over the last few years, several storage diseases have been treated with hematopoietic stem cell transplantation (HSCT). [3][4][5][6] The enzymatic activity of white blood cells has been proven to rise to normal levels after HSCT.…”
mentioning
confidence: 99%